Implementasi Kebijakan Peraturan Bupati Pamekasan Nomor 20 Tahun 2019 Tentang Penyelenggaraan Mal Pelayanan Publik - Ertien Rining Nawangsari; Paramitha, Audrey Nola (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Public Service Mall (MPP) is a place where public services from various government and private agencies are integrated in one place. The Public Service Mall (MPP) concept was adopted from Georgia's Public Service Hall (PSH). In Indonesia, there are currently 206 Public Service Malls. The existence of this MPP is expected to provide convenience, speed and comfort for the public in obtaining services. The aim of the research is to find out how to implement Pamekasan Regent Regulation Policy Number 20 of 2019 concerning the Implementation of Public Service Malls. The research method used is descriptive qualitative with data collection methods through interviews, observation and documentation. Data analysis in this research is through data collection, data condensation, data presentation and drawing conclusions. This research uses implementation theory according to Donald S. Van Meter & Van Horn which consists of six, namely policy standards and targets, resources, communication between organizations, characteristics of implementing organizations, social, economic and political conditions, attitudes/dispositions of executives. The results of the research show that the implementation of PERBUP Pamekasan Policy Number 20 of 2019 has gone well. Keywords: Policy Implementation; Public Services; Public Services Mal